The Relationship Among Seventh Grade Students' Participation in Online Games, English Vocabulary Mastery, and Learning Motivation - Lestari, Eva Fidia; Firdaus, Masagus; Yukamana, Hanni (JET (Journal of English Teaching), 2024)
The pandemic has affected many aspects of our lives including education and that has caused the Government to provide alternative teaching methods and make recommendations for online learning. Since smartphones and laptops using the internet are the only tools for learning, students are increasingly playing online games and being exposed to English vocabulary. This research aimed at identifying and analyzing whether students' participation in online games and vocabulary mastery simultaneously correlate with their learning motivation. This research is a quantitative research with a correlation design. The research was conducted at SMPN I Koba, Central Bangka, Bangka Belitung, with 93 students as respondents. The data collection technique used a questionnaire with a Likert scale on the online games questionnaire and learning motivation and the Guttman scale on the vocabulary mastery questionnaire. The prerequisite test uses the normality test, homogeneity test, and linearity test. Analysis using correlation analysis of r-Product moment and multiple regression analysis. The research results have shown that there is a correlation between students’ participation in online games and vocabulary mastery simultaneously with learning motivation.